Supporting children’s wellbeing through outdoor time: opportunities to integrate consistent outdoor time into the elementary school day - Patchen, Amie K.; Edwards, Amanda; Rakow, Donald A.; Meredith, Genevive R. (Frontiers in Public Health, 2024)
BackgroundTime in nature supports cognitive, psychological, academic, and health benefits. Outdoor time during school can provide young people with equitable access to these benefits, however, there are within-school constraints. Understanding if and how teachers can frequently and consistently incorporate outdoor time in the schoolyard into their classroom activities can inform broader implementation.MethodsA mixed-methods observational study was conducted with 17 teachers from five elementary schools. Teachers reported on how they incorporated outdoor time into their classes over an eight-week period. Data on outdoor time, activities, locations, barriers, motivations, and facilitators were collected through surveys on 15 randomly pre-selected days, and through a post-survey.ResultsOn the 15 randomly selected days surveyed, classes went outside 78% of the time, ranging from 6–15 outdoor days per class, and 0–285 min per day. Time, activities, locations, motivations, barriers, and facilitators varied across classes and days. The most common activities were free play (n = 138) and intentional engagement with nature (n = 57). Health benefits (n = 68) and having time (n = 58) were the most common motivations teachers reported for incorporating outdoor time.Implications for school health, policy, practice, and equityConsistent outdoor time in the school day can support students’ wellbeing and academic success. Encouraging free play, highlighting the health benefits, using a systems approach, and flexible implementation may help teachers increase their use of outdoor time during the school day.ConclusionTeachers consistently incorporated outdoor time, but implementation varied across classes and days. Implementation findings from this district could help inform practices at other schools.